THE EFFECT OF SCHOOL FACILITIES ON STUDENTS’ LEARNING MOTIVATION ON ENGLISH - Nabilla Dwi Hardiana; Natasya Aisyah; Natasya Herza Harahap; Emilya Sukma Dara (Universitas Maritim AMNI Semarang, 2023)
School facilities are a very important tool in supporting learning in schools. Facilities will be needed by teachers and students in teaching and learning because the facilities will increase students' learning motivation, with complete facilities will also support the performance of teachers in delivering material to students. The purpose of this study is to observe school facilities, especially MTS Ali Imron and see the effect of students' learning if the school facilities are inadequate, especially in English subjects. The case study in this study was conducted at MTS Ali Imron Medan. The method in this study uses a qualitative method by observing schools and conducting interviews with English teachers at MTS Ali Imron Medan.